2015
DOI: 10.1007/s00404-015-3639-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical pregnancy and spontaneous abortion in first IVF cycles are negative predictors for subsequent cycles: an over 10,000 cases cohort study

Abstract: BP and SA in first IVF cycles had negative predictive value for subsequent ART outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Previous studies have reported chance of live birth in IVF after miscarriage, but did not report CLBRs. Some reported the results of one subsequent cycle rather than CLBRs over multiple subsequent cycles (Croucher et al 1998, Kalu et al 2011, Yang et al 2015, while others reported live birth rate per oocyte retrieval, but could not report cumulative rates as there was no connection between woman and cycle (Kupka et al 2004). CLBRs report success over complete cycles of continued treatment more accurately than single cycle live birth rates, and are seen as a better measure for counselling couples on chances of success in future cycles (Stern et al 2010).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported chance of live birth in IVF after miscarriage, but did not report CLBRs. Some reported the results of one subsequent cycle rather than CLBRs over multiple subsequent cycles (Croucher et al 1998, Kalu et al 2011, Yang et al 2015, while others reported live birth rate per oocyte retrieval, but could not report cumulative rates as there was no connection between woman and cycle (Kupka et al 2004). CLBRs report success over complete cycles of continued treatment more accurately than single cycle live birth rates, and are seen as a better measure for counselling couples on chances of success in future cycles (Stern et al 2010).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Previous work has identified some of the risk factors associated with miscarriage including increasing maternal age (Baker et al 2010, Croucher et al 1998, Hipp et al 2016, previous miscarriages and polycystic ovary syndrome (Joham et al 2014, Knudsen et al 1991, Kupka et al 2004, Rai and Regan 2006. IVF-specific risk factors include the transfer of cryopreserved embryos, cleavage-stage embryo transfer, decreased response to ovarian stimulation (linked to maternal age), previous miscarriages in IVF conceptions and certain causes of infertility such as uterine factor and endometriosis (Croucher et al 1998, Hipp et al 2016, Kupka et al 2004, Yang et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…has not yet gained popularity due to low clinical pregnancy rate [5][6]. According to relevant literatures, 60% of all failures of in vitro fertilization-embryo transfers (IVF-ETs) are attributed to diminished endometrial receptivity [7].…”
Section: Introductionmentioning
confidence: 99%